RESEARCH ON MUSEUM CULTURAL AND CREATIVE PRODUCT FROM THE PERSPECTIVE OF NARRATIVE DESIGN AND ATMOSPHERIC AESTHETICS - JIANG , Y.; PASHKEVYCH, K. L. (Art and Design, 2023)
The purpose of the study is to explore how to uncover the aesthetic value of museum cultural and creative products and create an atmosphere through narrative design from the perspective of atmospheric aesthetics, to meet users’ daily aesthetic needs and contribute to the further development of museum education. The research methodology is interdisciplinary. This study adopts atmospheric aesthetics as the research perspective and combines a literature review and empirical research to elaborate on the subject. The research provides a comprehensive analysis of the narrative elements and characteristics of museum cultural and creative products, proposes narrative design approaches, and explores the elements, methods, and strategies of narrative design in depth. In this study, the narrative design strategy of museum cultural and creative products is discussed from the perspective of atmospheric aesthetics, and a narrative model of museum cultural and creative product design from the perspective of atmospheric aesthetics is constructed. By exploring in depth the aspects of museum cultural and creative products, such as the meaning of form and spirit, and the emotive narrative language, we can better understand the importance and value of museum cultural and creative products in contemporary society. These narrative strategies will not only enable people to better understand and appreciate the cultural connotations of cultural relics but also bring museums closer to the general public and promote cultural heritage and aesthetic education.